Report writing - Reid, Michelle (Palgrave Macmillan, 2012)
Includes bibliographical references and index; The Purpose of Reports -- Gathering Your Information -- Structuring Your Report -- Business Plans, Project Proposals and Dissertations -- Presenting Your Findings -- Writing Concisely -- Report Writing at Work